Design and construction of the dosing module for a coffee processing machine (2017)
"This document details the design and construction of the dosing module for a coffee processing machine. This module functions within a machine whose purpose is to process coffee, beginning with the untoasted grains and finishing with a grinded and packaged product. This module's function is to receive quantities of coffee beans of up to 1 kg from the flavoring module and delivering quantities of 35 grams to the grinding module. This document explains the design and construction process, which starts with the client's requirements and ends with the built machine. The result of this process is a machine that can't carry out its objective as it gets blocked when processing the coffee beans."--Tomado del Formato de Documento de Grado.